A NEW POSTGRADUATE SCHOOL MODEL: PRO ET CONTRA - B. I. Bednyi (Высшее образование в России)
This article analyzes and summarizes the opinions and assessments of experts in the field of higher education regarding the new model of training and certification of academic staff in the postgraduate school. Particular attention is given to the target functions of postgraduate school and to the improving its efficiency. We substantiate the approach to implementation of the postgraduate school’s main functions, which is focused on the market of highly intellectual labor, including its academic segment. It is shown that due to the expansion of the range of graduates’ professional trajectories, it is necessary to create dedicated postgraduate programs whose contents should be coordinated with specific employers. While an academic degree is an appropriate evidence of professional qualification for postgraduate students who are planning to pursue a career in the field of science and higher education, for those outside the academic market it is advisable to use a system for assessment of professional competencies and achievements that involves the award of professional degrees (e.g., in the field of public administration, management and business, education). The reasons are considered for the relatively low efficiency of postgraduate education as an institution with regard to reproduction of HR potential of science and higher education, which is its main function. Some measures aimed at improving the efficiency of academic postgraduate programs are also discussed.